The role of institutions in promoting a favorable business environment: an experimental approach - Oliveira, Charles Bonani de (2023)
Institutions significantly shape the business environment and foster entrepreneurship through regulations and implicit norms, forming the core for economic activities, including entrepreneurial endeavors. Institutions not only mold the uncertainty landscape for entrepreneurs and managers but also steer their decisions and actions. The intricate interplay among institutions, socio-cognitive attributes, politics, and innovation merits further scholarly exploration, revealing the intricate relationships that drive entrepreneurial ecosystems. This thesis contributes by providing novel insights into institutional roles in business environments. Institutions encompass formal and informal aspects, establishing the bedrock of shared social norms that inherently impact political, economic, and social interactions.